Determination of energy efficiency of autonomous generating equipment of industrial parks in conditions of military aggression - Zaichenko, Stefan; Derevianko, Denys; Kulish, Roman (Technology audit and production reserves, 2023)
The work considers the problem of determining the factors of energy efficiency of industrial parks in the conditions of military aggression in the conditions of the introduction of the National Economic Strategy and regulatory influence on Industrial Parks in Ukraine. The energy efficiency of industrial parks primarily depends on the main parameters of the selected technological processes that are embedded in the basis of enterprises and their productivity. A significant factor affecting the environmental friendliness and energy efficiency of industrial parks is the method of energy generation. On the basis of the analysis of the work of enterprises operating in conditions of military aggression, the main factors determining the energy efficiency of electricity production have been determined. Such factors are the overall efficiency of the power generating unit, which is determined by monitoring and diagnosing the power unit. Analyzing changes in energy efficiency, the characteristics of the power part of one of the most powerful diesel engines were selected. It is obvious that the diesel locomotive will consume more fuel to generate energy with a decrease in efficiency. The main diagnostic factors of generating equipment that affect the energy efficiency of industrial parks in conditions of military aggression are: the ratio of currents in compressor and depressurized modes, the real degree of compression, and as a result, the efficiency of the power plant. On the basis of the determined factors, the effectiveness of the implementation of the system of monitoring and diagnosing the power units of energy-generating equipment of enterprises in the conditions of military aggression was determined. Recommendations have been established to minimize fuel consumption and reduce emissions to ensure the main principles of industrial parks, environmental friendliness and energy efficiency.